Developing a blockchain framework for the automotive supply chain: A systematic review - Raj Kumar Reddy, Kotha; Gunasekaran, Angappa; Kalpana, P.; Raja Sreedharan, V.; Arvind Kumar, S (Computers & industrial engineering, 2021)
•Blockchain technology (BCT) in Automotive Supply Chain (ASC) is reviewed.•Exemplified the potential ASC activities for BCT adoption.•A blockchain framework is proposed to digitise and decentralize ASC activities.•Proposed an BCT implementation framework for ASC in VUCA world. As world is affected by demand volatility; process uncertainty; supply chain complexity and information ambiguity forming a VUCA world. To manage this scenario, industries are adopting emerging technologies for business excellence and one among them is Blockchain. Blockchain technology (BCT) is a distributed ledger technology (DLT) that stores transactional records in a tamper-proof and immutable way; it is a promising solution for incorporating transparency and traceability in traditional ecosystem. As automotive industries are facing a Volatile environment, Uncertain schedules & information; Complex supply chain networks, and Ambiguous decisions that cripples the automotive supply chain (ASC). Therefore, BCT can be used to address issues related to ASC in VUCA world. Keeping this in mind, study reported a systematic literature review (SLR) of BCT applications in ASC. More than seventy research papers were reviewed based on different BCT characteristics and applications. Through content analysis, study explored how to link supply chain visibility, information transparency with BCT for an efficient ASC in VUCA world. Moreover, a BCT implementation framework is proposed for ASC, to provide a decision-making approach for practitioners in VUCA world.